Induction of resistance of Podosphaera xanthii (hull-less pumpkin powdery mildew) to triazole fungicides and its resistance mechanism. - Qiaolan Liang; Liexin Wei; Bingliang Xu; Jia Liu; Shuwu Zhang; Lilong Liu (PLoS ONE, 2022)
The aim of this study was to uncover the molecular mechanism through which fungicide resistance develops in Podosphaera xanthii, a fungi that causes powdery mildew in hull-less pumpkin. Treatments of inoculated P. xanthii were carried out on leaves of hull-less pumpkin and subsequently treated with kinds of triazole fungicide for seven generations. Resistant strains of P. xanthii thus obtained were evaluated for their resistance levels. The resistance levels of the fungi to four fungicides of were high except that of the propiconazole-resistant strain, which showed moderate resistance. The F7 generations of five resistant strains thus obtained were cultured continuously for five generations without fungicide induction, and their resistance level were found to be relatively stable. The DNA of the sensitive strain and the five kinds of resistant strains were extracted by the sodium dodecyl sulfate (SDS) method and its internal transcribed spacer (ITS) region was amplified by using ITS1/ITS4 primer and specific primer F/R and they were sequenced respectively. The DNA sequence comparison of resistant and sensitive strains showed that the base pairs of tebuconazole-resistant strains and flusilazole-resistant strains were mutated, with mutation rates of 4.8% and 1.6%, respectively. The base pairs of the other three resistant strains did not change.